The Influence of K-Pop Idol Brand Ambassadors, FOMO Phenomenon, and Consumer Loyalty on Purchase Intention: A Case Study of the Barenbliss × Hearts2Hearts Collaboration - Yasmina Diani Hanafiah; Tanti Sugiharti; Ria Wulandari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of Brand Ambassador, the Fear of Missing Out (FOMO) phenomenon, and Consumer Loyalty on Purchase Intention toward Barenbliss x Hearts2Hearts collaborative products. The research adopts a quantitative approach using a survey method to obtain primary data. A total of 100 respondents were selected through purposive sampling, consisting of users or potential users of Barenbliss cosmetic products as well as fans of Hearts2Hearts who are familiar with the collaboration. Data were collected through structured questionnaires designed to measure perceptions of the Brand Ambassador, the level of FOMO experienced by consumers, consumer loyalty, and their intention to purchase the products. The collected data were analyzed using multiple linear regression analysis supported by classical assumption tests, including normality, multicollinearity, and heteroscedasticity tests, with the assistance of SPSS version 29. The results of the analysis reveal that Brand Ambassador (X1), FOMO Phenomenon (X2), and Consumer Loyalty (X3) each have a positive and significant effect on Purchase Intention (Y), indicating that all partial hypotheses are accepted. This finding suggests that the presence of an influential brand ambassador, consumers’ fear of missing out on popular products, and strong loyalty toward the brand play important roles in shaping purchase intention. Furthermore, the simultaneous test results demonstrate that the three independent variables collectively have a positive and significant effect on Purchase Intention toward Barenbliss x Hearts2Hearts products. Therefore, the simultaneous hypothesis is also accepted, confirming that the integration of these factors effectively drives consumer purchase intention.